PENERAPAN METODE KERJA KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V C SD NEGERI 004 TEMBILAHAN KECAMATAN TEMBILAHAN - Siti Arfiah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low grade science students learning outcomes V C SD Negeri 004 Tembilahan. This is evidenced from 42 students only 18 students (42.86%) who achieved a minimum completeness criteria (KKM). In addition, the average learning results obtained remainder is equal to 62.18. Based on this, researchers conducted a study to implement group work method. The purpose of this research is to improve student learning outcomes IPA. This research is a class act, who performed a total of two cycles, each cycle consisting of two meetings. The subjects were students of class V C SD Negeri 004 Tembilahan by the number of students 42 students. The study states that science learning outcomes in each cycle has increased. In preliminary data the average learning results obtained are 62.18 by the number of students who completed is 18 students (42.86%). On average the first cycle of learning outcomes increased to 72.18 by the number of students who completed the 36 Siwa (80.95%), and the second cycle increased the average achieved learning outcomes 80.38 by the number of students who completed totaling 42 students (100%). Based on the results of this study concluded that the application of group work methods to improve learning outcomes fifth grade science students SD Negeri 004 Tembilahan.